Role of Streptococcus Anginosus on the formation of dental caries - Nonong, Yetty Herdiyati; Satari, Mieke Hemiawati; Sasmita, Inne Suherna (Padjadjaran Journal of Dentistry, 2011)
Generally, the etiology of dental caries is the cariogenic properties of bacteria, these are always associated with Streptococcus mutans. Glucosyltransferase fragment (Gtf) are also in other strains of Streptococcus such as Streptococcus anginosus, Streptococcus milleri which includes beta hemolysis. Genotypically B Streptococcus anginosus has genetic characteristics that are similar to Streptococcus mutans. The research objective was to determine the existence of Gtf B/C gene as a cause of caries in Streptococcus anginosus. The study was conducted in experimental laboratories with PCR technique by taking a sample of 20 children who had caries. The results showed there was the amplification of Streptococcus anginosus with a level of homology 96%, 97%, and 99%. The results of the Gtf genes amplification fragment B/C provided 600 pb ribbon. The conclusion was Streptococcus anginosus classified as cariogenic bacteria because they had Gtf B/C genes.